ACHIEVING HAIR SALON COMPETITIVENESS THROUGH RELATIONSHIP MARKETING MODEL: A CASE OF HAIR SALONS IN THE FREE STATE PROVINCE IN SOUTH AFRICA - Dr Francis Okyere,; Dr Edmund Owusu Amoakoh, (IJRDO - Journal of Business Management, 2019)
This paper is based on research on growing competition within hair salons. The study found evidence of such competition and identified relationship marketing (RM) as a tool to support competitive strategy. Hair salons are regarded as emerging small, medium and micro enterprises (SMMEs) – a status achieved due to participation in competitive social-economic activities. This paper presents a RM model compatible with the requirements of emerging SMMEs. It is hoped that this model will promote hair salons’ competitive strategy, thus contributing to South African socio-economic mantra. There is a perceived lack of relationship marketing by SMMEs, particularly for emerging SMMEs like the hair salons. This perception amplifies the importance of strategic tools to support competitive strategy for successful competition. A survey data collection method was used to collect quantitative and qualitative data from 145 respondents, randomly selected owner/managers of hair salons and customers. These responses were supported with personal interviews to improve generalizability. The evidence of lack of awareness and the importance of RM activities was found. This finding supports the need for RM model presentation and hair salon competitiveness and emphasises the requirements for hair salons as emerging SMMEs.